Challenges to surface water quality in mid‐sized African cities: conclusions from Awetu‐Kito Rivers in Jimma, south‐west Ethiopia. (12th December 2012) - Haddis, Alemayehu; Getahun, Tadesse; Mengistie, Embialle; Jemal, Amana; Smets, Ilse; van der Bruggen, Bart
Abstract Rapid urbanization and industrialization, uncontrolled population growth, indiscriminate waste discharge and poor infrastructure are problems that African cities are facing. This paper describes an exemplary case study from Jimma, south‐west Ethiopia. A cross‐sectional study was conducted along the Awetu‐Kito drainage system in Jimma town to assess the level of pollution from urban dwellers and related activities. The study indicates that the Environmental Protection Agency (EPA) norms for biochemical oxygen demand (BOD), dissolved oxygen (DO) and orthophosphates are not met downstream of the major industrial and institutional activities. Small‐scale industries, Jimma University and residential areas contributed 50, 15 and 23% pollution load on the river, respectively. It can be concluded that the pollution effect in Jimma town is mainly as a result of the growing (uncontrolled) industrial activities and not to discharge of household wastewater. Given the same trends of urbanization and population growth, similar development (socio‐economic) indicators and similar climatic conditions, the key findings for Jimma are transferable to other mid‐sized African cities.